Learning Compassion and Meditation: A Mixed-Methods Analysis of the Experience of Novice Meditators - Mascaro, Jennifer S.; Florian, Marianne P.; Ash, Marcia J.; Palmer, Patricia K.; Sharma, Anuja; Kaplan, Deanna M.; Palitsky, Roman; Grant, George; Raison, Charles L. (Frontiers in Psychology, 2022)
Over the last decade, numerous interventions and techniques that aim to engender, strengthen, and expand compassion have been created, proliferating an evidence base for the benefits of compassion meditation training. However, to date, there is little consensus about the sources and mechanisms that lead to different outcomes across individuals and little research has been conducted to examine individual variation in the learning, beliefs, practices, and subjective experiences of compassion meditationthe process of learning that occurs during compassion meditation training. This mixed-method study examines changes in novice meditators’ knowledge and contemplative experiences before, during, and after taking an intensive course in CBCT® (Cognitively-Based Compassion Training), a contemplative intervention that is increasingly used for both inter- and intrapersonal flourishing. The participants in this study (n=40) were Christian healthcare chaplains completing a one-year residency in Clinical Pastoral Education (CPE) who learned CBCT as part of their professional chaplaincy training curriculum. Prior to and upon completion of training, we surveyed participants to assess their beliefs about the malleability of compassion, levels and types of engagement in compassion meditation, and perceptions of the impact of taking CBCT®. We also conducted in-depth interviews with a subset of participants to gain a richer qualitative understanding of their subjective experiences of learning and practicing compassion meditation, a key component of CBCT. We found that participants reported increases in the extent to which they believed compassion to be malleable after studying CBCT. We also found high levels of variability of individual ways of practicing and consider the implications of this for the study of contemplative learning processes. This multi-methodological approach yielded novel insights into how compassion practice and compassion-related outcomes interrelate, insights that can inform the basic scientific understanding of the experience of learning and enacting compassion meditation as a means of strengthening compassion itself.